2013
DOI: 10.5334/ijic.1412
|View full text |Cite
|
Sign up to set email alerts
|

Lochaber telemedicine clinic – A new approach managing dementia in care homes

Abstract: Introduction: With an estimated 4000 people currently living with dementia in the Highlands of Scotland and predictions of a 100% increase in incidence in the next 20 years, there are significant challenges facing NHS Older Adult Psychiatry services and Care Home providers. Geographic dispersal and rurality add to the difficulties of providing a community based, quality service. Creative and innovative responses require to be found to meet these increasing demands. When patients were reviewed face to face ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Table 2 shows the papers grouped by country of origin. Twelve of the identified papers originated from the USA [ 32 , 38 , 39 , 43 , 45 , 48 51 , 54 , 55 , 59 ]; five were from China [ 31 , 44 , 53 , 56 , 60 ], three were from the UK [ 47 , 52 , 58 ], and three from Australia [ 33 , 42 , 57 ]. The remaining three papers were from Korea [ 40 ], Sweden [ 46 ], and France [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 shows the papers grouped by country of origin. Twelve of the identified papers originated from the USA [ 32 , 38 , 39 , 43 , 45 , 48 51 , 54 , 55 , 59 ]; five were from China [ 31 , 44 , 53 , 56 , 60 ], three were from the UK [ 47 , 52 , 58 ], and three from Australia [ 33 , 42 , 57 ]. The remaining three papers were from Korea [ 40 ], Sweden [ 46 ], and France [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Table 3 shows the breakdown of papers by study design. The most frequently reported method was case studies, with 14 of the papers describing the use of this design [ 31 , 33 , 38 , 44 , 45 , 47 51 , 55 , 57 , 59 , 60 ]. Five cohort studies were identified looking at general practitioner adherence to assessments undertaken during consultations [ 41 ], videoconferencing for the diagnosis of dementia [ 54 ], and the use of 24-hour consultations [ 52 ] and for the care of dementia patients in Korea [ 40 ] and one looking at the implementation of videoconferencing in long-term care [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…All of the 38 UK studies were published after 2010. They comprised 14 reviews or reports relating to technology and care homes, 21,22,[27][28][29]35,83,96,99,170,208,234,254,267 three case studies, 80,134,246 three qualitative studies, 115,124,194 two observational studies, 16,139 one pilot RCT, 277 one protocol, 45 12 descriptive studies 58,59,71,109,113,123,188,195,207,223,242,284 and two opinion pieces. 34,53 Telehealth and surveillance technologies were both the subject of six articles, 16,71,113,115,195,234 and single articles were identified on gaming, 125 robots, 80 digital records 134 and communication technologies.…”
Section: Countriesmentioning
confidence: 99%
“…This will necessitate the development and assessment of innovative methods for delivering efficient health care in care homes [4]. Videoconferencing has been trialled in care homes in a range of countries with the aim of improving resident access to health care for a wide range of purposes, such as; assessment [2][3][4][5][6][7][8][9], management [10][11][12][13][14] and diagnosis [15]. Associated evaluation and research has looked at a range of clinical outcomes such as; hospital admissions [3,[16][17][18][19][20], A&E attendances [21] and medication use [13], with the main body of evidence originating from America [2,3,8,9,[12][13][14][15]19,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Three papers identified in the scoping review explored the use of videoconferencing in the UK [11,18,20], with two looking at videoconferencing in care homes for older adults [18,20] and one looking at the use of it in psychiatric patients [11]. Both Pope et al (2013) and Hex (2015) found videoconferencing reduced health care costs and emergency department attendances.…”
Section: Introductionmentioning
confidence: 99%